(untitled) (Journal of Engineering and Health Sciences, 2020)
Sea cucumber or locally known as gamat and timun laut is a well-known attraction of Pulau Langkawi, Kedah, Malaysia. Not only limited to Pulau Langkawi, sea cucumber can also be found in other coastal water areas of Malaysia. However, the species richness and genetic diversity of sea cucumber in Pulau Tinggi, Johor is still unknown to the marine scientific communities, especially for Holothuria (Mertensiothuria) leucospilota, the most dominant species in Malaysia. Therefore, this study aimed to generate DNA barcodes of H. leucospilota from Pulau Tinggi. Protein-coding cytochrome c oxidase 1 (CO1) mtDNA gene was used as it is commonly and widely used for molecular species identification via DNA barcoding. Polymerase chain reaction (PCR) and DNA sequencing were incorporated to generate the DNA barcodes of CO1 mtDNA gene. The BLAST program confirmed the species status of the sea cucumber specimens as H. leuscospilota or locally known as bat puntil or white threads fish. The application for GenBank, NCBI, U.S. National Library of Medicine registration was successfully accepted on October 17, 2019 with accession numbers of MN580537 and MN580538). The phylogenetic trees i.e neighbor joining tree (NJ, distance-based method), maximum parsimony tree (MP, character-based method) and maximum likehood tree (ML, character-based method) reconstructed using MEGA X software version 10.0.5 (BETA) further supported the species status of the sea cucumber specimens from Pulau Tinggi as H. leuscospilota. This is the first record of CO1 mtDNA barcodes of H. leuscospilota from Pulau Tinggi, Johor, Malaysia.